Solve for a (complex solution)
\left\{\begin{matrix}a=\frac{1}{x}\text{, }&x\neq 0\\a\in \mathrm{C}\text{, }&b=\frac{1}{x}\text{ and }x\neq 0\end{matrix}\right.
Solve for b (complex solution)
\left\{\begin{matrix}b=\frac{1}{x}\text{, }&x\neq 0\\b\in \mathrm{C}\text{, }&a=\frac{1}{x}\text{ and }x\neq 0\end{matrix}\right.
Solve for a
\left\{\begin{matrix}a=\frac{1}{x}\text{, }&x\neq 0\\a\in \mathrm{R}\text{, }&b=\frac{1}{x}\text{ and }x\neq 0\end{matrix}\right.
Solve for b
\left\{\begin{matrix}b=\frac{1}{x}\text{, }&x\neq 0\\b\in \mathrm{R}\text{, }&a=\frac{1}{x}\text{ and }x\neq 0\end{matrix}\right.
Graph
Share
Copied to clipboard
abx^{2}-\left(ax+bx\right)+1=0
Use the distributive property to multiply a+b by x.
abx^{2}-ax-bx+1=0
To find the opposite of ax+bx, find the opposite of each term.
abx^{2}-ax+1=bx
Add bx to both sides. Anything plus zero gives itself.
abx^{2}-ax=bx-1
Subtract 1 from both sides.
\left(bx^{2}-x\right)a=bx-1
Combine all terms containing a.
\frac{\left(bx^{2}-x\right)a}{bx^{2}-x}=\frac{bx-1}{bx^{2}-x}
Divide both sides by bx^{2}-x.
a=\frac{bx-1}{bx^{2}-x}
Dividing by bx^{2}-x undoes the multiplication by bx^{2}-x.
a=\frac{1}{x}
Divide -1+bx by bx^{2}-x.
abx^{2}-\left(ax+bx\right)+1=0
Use the distributive property to multiply a+b by x.
abx^{2}-ax-bx+1=0
To find the opposite of ax+bx, find the opposite of each term.
abx^{2}-bx+1=ax
Add ax to both sides. Anything plus zero gives itself.
abx^{2}-bx=ax-1
Subtract 1 from both sides.
\left(ax^{2}-x\right)b=ax-1
Combine all terms containing b.
\frac{\left(ax^{2}-x\right)b}{ax^{2}-x}=\frac{ax-1}{ax^{2}-x}
Divide both sides by ax^{2}-x.
b=\frac{ax-1}{ax^{2}-x}
Dividing by ax^{2}-x undoes the multiplication by ax^{2}-x.
b=\frac{1}{x}
Divide -1+ax by ax^{2}-x.
abx^{2}-\left(ax+bx\right)+1=0
Use the distributive property to multiply a+b by x.
abx^{2}-ax-bx+1=0
To find the opposite of ax+bx, find the opposite of each term.
abx^{2}-ax+1=bx
Add bx to both sides. Anything plus zero gives itself.
abx^{2}-ax=bx-1
Subtract 1 from both sides.
\left(bx^{2}-x\right)a=bx-1
Combine all terms containing a.
\frac{\left(bx^{2}-x\right)a}{bx^{2}-x}=\frac{bx-1}{bx^{2}-x}
Divide both sides by bx^{2}-x.
a=\frac{bx-1}{bx^{2}-x}
Dividing by bx^{2}-x undoes the multiplication by bx^{2}-x.
a=\frac{1}{x}
Divide -1+bx by bx^{2}-x.
abx^{2}-\left(ax+bx\right)+1=0
Use the distributive property to multiply a+b by x.
abx^{2}-ax-bx+1=0
To find the opposite of ax+bx, find the opposite of each term.
abx^{2}-bx+1=ax
Add ax to both sides. Anything plus zero gives itself.
abx^{2}-bx=ax-1
Subtract 1 from both sides.
\left(ax^{2}-x\right)b=ax-1
Combine all terms containing b.
\frac{\left(ax^{2}-x\right)b}{ax^{2}-x}=\frac{ax-1}{ax^{2}-x}
Divide both sides by ax^{2}-x.
b=\frac{ax-1}{ax^{2}-x}
Dividing by ax^{2}-x undoes the multiplication by ax^{2}-x.
b=\frac{1}{x}
Divide -1+ax by ax^{2}-x.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}